Estudo da adição de sais e variação da umidade na obtenção de fibras de Ecovio® por eletrofiação - Meira, Ana Caroline Reis (2019)
The aim of this study was to evaluate the mechanical and morphological characteristics of the Ecovio® fibers obtained by electrospinning, altering parameters such as relative humidity (U.R.) and adding salts to the polymer solution. In order to do so, was determined, in an exploratory approach, the conditions to obtain pure polymer fibers, changing parameters , for instance, the concentration of the polymer in the solution, distance between the needle tip and the collector, applied voltage and solution ejection flow, being the ideal conditions reached with 15% (m.v-1) of Ecovio® in chloroform/dimethylformamide solution 85/15 ( v/v), 12 cm the distance between the needle tip and the collector, 14 kV applied voltage and flow rate of 1 mL.h-1. The study of the addition of salts to the polymer solution was accomplished through the addition of 0.225 g metformin hydrochloride (Met), CaCl2 or NaCl and the effects caused by the increase of the relative air humidity was evaluated using 30% and 80% moisture content. The fibers containing salts were washed and dried at room temperature and the films analyzed by means of Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analyzes (TGA / DTGA), X-ray Diffraction (XRD), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), Contact Angle, Mechanical Analysis and the porosity and mean interfiber pore size were measured with method Brunauer–Emmett– Teller (BET), enabling to observe the salt presence and absence, before and after the films washing, changes in the interactions between the monomers of the blend and decrease of the diameter of the fibers due to the presence of the salt in the polymer solution. The effect of moisture caused a significant increase in the porosity of the Ecovio® obtained with UR 80%, reducing the material resistance and giving a 250% increase in the surface area of the same, similar behavior was not observed for the fibers treated with the salts, where the increase in moisture also enhanced the strength of fibers which presented a larger diameter. In accordance with the analyzes, changes were observed in the mechanical and morphological characteristics of the Ecovio® fibers obtained by electrospinning caused by U.R. variation and addition of salts to the polymer solution.